Analysis of the microbial communities of three kinds of Fen‐Daqu by PLFAs. Issue 1 (6th January 2016) - Zhang, Hongxia; Zhang, Xiuhong; Zhao, Jinglong; Du, Xiaowei; Ma, Bing
Abstract : In order to find a suitable method for detecting the microbe index of Daqu for Chinese liquor brewing, during the regular production of Daqu, the phospholipid fatty acid (PLFA) profiles of Daqu for light‐fragrant Chinese liquor were investigated. Three types of Daqu clearly showed different features. The PLFA 18:3 w 6c (3, 6, 9), as one of the biomarkers for fungi, was the highest in the Houhuoqu samples, the lowest in the Hongxinqu samples and moderate with fluctuations in the Qingchaqu samples. The PLFA 18:1 w 9c, another biomarker for fungi, was only detected in the Hongxinqu samples with a steady content. The ratio of the fungi to bacteria of Hongxinqu was 11:20, which was significantly higher than in the Qingchaqu and the Houhuoqu samples. Principal component analysis found that most of the variations in the PLFA patterns were due to the different Daqu types. Variances analysis found that some PLFAs had the potential to be used as representative biomarkers for each type of Daqu. Copyright © 2016 The Institute of Brewing & Distilling